2019
DOI: 10.5999/aps.2018.00535
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mini-open carpal tunnel release: An outcome study

Abstract: Background Carpal tunnel syndrome (CTS) is the most common peripheral entrapment neuropathy with a high morbidity and healthcare-related costs. Currently there is no consensus about the best treatment option. The purpose of this prospective cohort study conducted at a single institution was to evaluate the clinical outcomes and patient satisfaction following a mini-open carpal tunnel release for idiopathic CTS. Methods A total of 72 patients (53 female and 19 male patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
(20 reference statements)
0
13
1
1
Order By: Relevance
“…Studies investigating open or endoscopic release of the carpal tunnel have reported advantages and disadvantages of each technique, and it is up to the surgeon to decide the surgical method 10 11 12 13 . Carpal tunnel release through a small incision, in which the TCL is incised through a minimal skin incision, alleviates the side effects and challenges of endoscopic decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating open or endoscopic release of the carpal tunnel have reported advantages and disadvantages of each technique, and it is up to the surgeon to decide the surgical method 10 11 12 13 . Carpal tunnel release through a small incision, in which the TCL is incised through a minimal skin incision, alleviates the side effects and challenges of endoscopic decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical intervention is a well-known and effective method of CTS treatment. Different surgical methods are considered: open, mini-open, and endoscopic decompression of the median nerve at the wrist ( 1 , 21 , 22 ). In all our patients, an open, minimally invasive method was performed, with a surgical incision above the flexor cord or on the level of the metacarpus with immediate neuromobilization and fitness exercises after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…However, endoscopic surgery potentially increases the risk of damage to the motor branch of the median nerve, and therefore most hand surgeons choose the open method. According to van den Broeke et al ( 22 ), the mini-open method probably needs a longer time for a good outcome than the standard period of 3 to 6 months and is normally characterized by persistent post-intervention complaints. Some reports consider the endoscopic technique to be better in terms of pain relief and patient satisfaction in the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Only one of the 28 cases involved a prominent, thick LABC. Increased attention is needed during nerve dissection, such as open and endoscopic carpal tunnel release [21,22], Camitz opponensplasty, or elevation of an iRASP flap. A neglected injury to the deep branch of the PCMN or the LABC is likely to cause discomfort.…”
Section: Discussionmentioning
confidence: 99%